PARAUROMASTYX GILMOREI GEN. ET SP. NOV. (ISODONTOSAURIDAE, IGUANIA), A NEW LIZARD FROM THE UPPER CRETACEOUS OF MONGOLIA - Alifanov V.R. (My University, 2004)
A new Late Cretaceous lizard, Parauromastyx gilmorei gen. et sp. nov., is described on the basis of a skull from the Bayn-Dzak locality (Mongolia). The new lizard along with Late Cretaceous Isodontosaurus gracilis Gilmore, 1943 and a number of problematic lizard species from the Paleogene of China are assigned to the family Isodontosauridae (Pachyglossa, Acrodonta, Iguania). The patterns of tooth attachment in lizards are discussed.
Keywords: lizard; Mesozoic::Cretaceous; Мезозой::Меловая